Ferroelectric Switching in Sub-20 nm Aluminum Scandium Nitride Thin Films - Wang, Dixiong; Zheng, Jeffrey; Musavigharavi, Pariasadat; Zhu, Wanlin; Foucher, Alexandre C.; Trolier-McKinstry, Susan E.; Stach, Eric A.; Olsson, Roy H. (IEEE electron device letters, 2020)
Ferroelectric switching was studied in 20 nm thick Al 0.68 Sc 0.32 N and Al 0.64 Sc 0.36 N films (with ~4 nm surface oxides) on platinized silicon wafers by multiple electrical characterization methods. Positive up negative down (PUND) measurements were conducted using 100 μs monopolar triangular waveform excitation. At room temperature, Al 0.68 Sc 0.32 N exhibited an apparent remanent polarization, P r = 140 μC/cm 2 and a coercive field, E c = 6.5 MV/cm, while film leakage prevented quantitative measurement of the Al 0.64 Sc 0.36 N ferroelectric properties. Remanent polarizations of 75 μC/cm 2 for Al 0.68 Sc 0.32 N and 25μC/cm 2 for Al 0.64 Sc 0.36 N were measured at 120 K. Partial ferroelectric switching was confirmed at room temperature for both materials via the measured transverse piezoelectric coefficients (e 31, f ) of -1.3 C/m 2 (down-switching) and -0.3 C/m 2 (up-switching) for Al 0.68 Sc 0.32 N, and -0.9 C/m 2 (down-switching) and -0.7 C/m 2 (up-switching) for Al 0.64 Sc 0.36 N.